2018
DOI: 10.7150/ijms.24146
|View full text |Cite
|
Sign up to set email alerts
|

Manual acupuncture relieves bile acid-induced itch in mice: the role of microglia and TNF-α

Abstract: Pruritus, or itch, is a frequent complaint amongst patients with cholestatic hepatobiliary disease and is difficult to manage, with many patients refractory to currently available antipruritic treatments. In this study, we examined whether manual acupuncture (MA) at particular acupoints represses deoxycholic acid (DCA)-induced scratching behavior and microglial activation and compared these effects with those induced by another pruritogen, 5'-guanidinonaltrindole (GNTI, a kappa opioid receptor antagonist). MA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 49 publications
(52 reference statements)
1
16
0
Order By: Relevance
“…Secondly, it could restore the normal function of microglia to reduce the inflammation. Studies have reported that acupuncture could alleviate spinal microglial activation to achieve the aim of reducing scratching behavior [43]. Furthermore, our previous study found that EA has such therapeutic effects on Alzheimer's disease mice, by promoting the polarization of microglia cells to neuroprotective M2 phenotype and inhibiting the information of cytotoxic M1 phenotype microglia cells [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, it could restore the normal function of microglia to reduce the inflammation. Studies have reported that acupuncture could alleviate spinal microglial activation to achieve the aim of reducing scratching behavior [43]. Furthermore, our previous study found that EA has such therapeutic effects on Alzheimer's disease mice, by promoting the polarization of microglia cells to neuroprotective M2 phenotype and inhibiting the information of cytotoxic M1 phenotype microglia cells [44].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence-Based Complementary and Alternative Medicine positive expression of hippocampus CA1 (Dss vs Con, 1.58 ± 0.31 vs 5.10 ± 0.59, P < 0.001), CA3 (2.34 ± 0.15 vs 5.04 ± 0.64, P < 0.01), and DG (1.91 ± 0.12 vs 3.76 ± 0.40, P < 0.01) (Figure 3) regions in the model group had statistical significance. However, the % area of GFAP positive expression markedly increased after EA (Dss + EA vs Dss, CA1: 7.25 ± 1 43. vs 1.58 ± 0.31, P < 0.01; CA3: 5.86 ± 1.07 vs 2.34 ± 0.15, P < 0.05; DG: 6.25 ± 0.83 vs 1.91 ± 0.12, P < 0.001) and moxibustion (Dss + Mox vs Dss, CA1: 4.73 ± 0.59 vs 1.58 ± 0.31, P < 0.01; DG (5.72 ± 0.63 vs 1.91 ± 0.12, P < 0.01) treatment, except for the expression of GFAP in hippocampus CA3 area after moxibustion treatment (3.67 ± 0.84 vs 2.34 ± 0.15, P > 0.05).…”
mentioning
confidence: 97%
“…LI4 is located on the first dorsal interossei, medial to the middle of the second metacarpal bone. The LI11 is located at the depression medial to the extensor carpi radialis, at the lateral end of the cubital crease 79 , 80 . Stainless steel acupuncture needles (Shanghai Yanglong Medical Articles Co., Ltd., Shanghai, China) measuring 0.2 mm in diameter and 2 cm in length were used in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Electrical stimulation (150-µs pulses at 2 Hz for 20 min) was applied via two needles inserted to a depth of 2–3 mm (Supplementary Fig. S9) using an electrical stimulator (Trio 300, Ito, Japan), as per the methodology described in a previous study 79 . Manual acupuncture (MA) was applied to the same acupoints (LI4 and LI11) without electrical stimulation.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have indicated that the mechanisms of chronic itch may involve sensitization of itch-signaling pathways ( Simone et al, 1991 ; Akiyama et al, 2012 ), so antihistamine medicine does not work well in chronic itch diseases. Lee et al (2018) found that electroacupuncture (EA) at Hegu (LI4) and Quchi (LI11) acupoints reduced scratching induced by 5’-guanidinonaltrindole [GNTI, a kappa opioid receptor (KOR) antagonist] in mice. Previous clinical and experimental studies have shown that EA can effectively reduce chronic itching caused by psoriasis, atopic dermatitis, urticaria, uremic pruritus, and other chronic allergic skin diseases ( Duo, 1987 ; Che-Yi et al, 2005 ; Kim et al, 2010 ; Jung et al, 2014 ; Wang et al, 2019 ; Zhang et al, 2020a , b ).…”
Section: Introductionmentioning
confidence: 99%